Cultural Politics in Revolution : Teachers, Peasants, and Schools in Mexico, 1930-1940 - Vaughan, Mary K., 1942- (Book collections on Project MUSE., 1997)
"Innovative study of the cultural legacy of the Mexican Revolution, using the story of rural schools. Focuses on Puebla and Sonora and the attempt by the central government to implement socialist education and to advance its nationalist agenda. Stresses the importance of negotiation among national and local leaders, teachers and peasants"--Handbook of Latin American Studies, v. 58.